Penerapan Constructive Controversy dan Modified Free Inquiry Terhadap HOTS Mahasiswa Pendidikan Biologi - Rosa Dewi Pratiwi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The aims of this study was to determine the effect of the using Constructive Controversy (CC) and Modified Free Inquiry (MFI) Method, analytical skill, and it’s interaction toward biology students’ cognitive learning achievement and HOTS. The method used in the research was experimental method and it was conducted from November 2013 to January 2014. The population was the biology students in UNINDRA. The sample was consisted of three class R3A, R3B and R3C. The learning method applied to R3A was MFI, R3B was control and to R3C was CC. The data was collected through students’ cognitive learning achievement test, analytical skills test, HOTS test, and supported by questioner for measuring affective achievements and observation sheet for assessing psychomotor. The hypothesis was tested using parametric statistic. The finding showed that: 1) There was significant difference from the results of two compared learning methods towards students’ cognitive learning achievement and HOTS, 2) Analytical skills affected students’ cognitive learning achievement and HOTS, 3) There was interaction between learning method and analytical skills toward student s’ cognitive learning achievement and HOTS.